Anti-Quorum Sensing in Pathogenic Microbes Using Plant-Based Bioactive Phytochemicals - Kumaran Subramanian; Harshni Selvaraj; Balakrishnan K; Pugazhvendan Sampath Renuga; Velmurugan S; Wilson Aruni (Advances in Materials Science and Engineering)
Infectious disease-causing pathogenic microorganisms grow rapidly within quorum sensing mediated biofilms. Attempts are made to restrict quorum sensing in pathogens, and the formation of biofilms has paved the way for the identification of bioactive phytochemicals. Anti-QS compounds have been proven to reduce bacterial pathogenicity in the past. Medicinal plants provide an enticing repertoire of phytochemicals with distinct microbial disease-controlling potential due to the vast spectrum of secondary metabolites included in extracts such as phenolics, quinones, flavonoids, alkaloids, terpenoids, and polyacetylenes. This review makes a specialty of the bioactive molecules produced using vegetation which have a target closer to quorum sensing accompanied via biofilm formation in pathogenic microbes.